Effects of semi-natural habitats on integrated pest management and biodiversity enhancement in arable agriculture - Earl, Robyn (The University of Edinburgh, 2025)
Semi-natural habitats are used under various names in agri-environment schemes. A recent iteration of the Common Agricultural Policy of the European Union designated some specific semi-natural habitats as Ecological Focus Areas (EFA). These were habitats and landscape features introduced to support biodiversity within agricultural landscapes. One potential EFA option was arable margins. These strips of grass and/or wildflowers are created alongside or surrounding an arable crop, occupying the outer edge of the field previously used for crop production. Research in other European countries on arable margins has shown they support local insect biodiversity and contribute to pest management; encouraging local populations of predatory species that can move into the adjacent crop and feed on pests. On a wider scale re-introducing semi-natural habitats such as arable margins to simplified agricultural landscapes has proved to effectively support insect biodiversity and halt decline. Where density of these semi-natural habitats is low, the insects dependent on them are forced to compete amongst each other for the limited resources available. Once the density of semi-natural habitat rises the competition eases and the insect populations are supported. This research supporting the implementation of arable margins has not yet been carried out in Ireland. The landscape that margins are implemented in is vulnerable: In Ireland these arable margins were implemented in cereal producing areas. These areas are predominantly in the east of the country where the decline of insect biodiversity is most pronounced compared to the west. Ireland’s insect diversity is limited to a lower number of species than even the closest neighbouring countries. Yet also has a seemingly dense network of hedgerows which may provide sufficient support for insect species, so the introduction of an arable margin may not make an apparent difference. With these differences in landscape and species richness, a key question is “will arable margins have similar beneficial effects, or different effects compared with other countries for both the biodiversity and potential pest control services?”. This thesis explores the impact of various vegetation mixes in arable margins on biodiversity and pest control support. It examines whether the introduction of arable margins in a landscape with declining biodiversity but also a dense hedgerow network can enhance biodiversity support. The study also investigates the effects of arable margins on overall invertebrate diversity and abundance, as well as on specific taxonomic groups with specialized resource requirements such as Carabidae and wild pollinators. Key findings show that different vegetation mixes provide varying levels of support for groups with specialized resource requirements. The results inform margin vegetation design to target specific conservation interests in the local environment. Pest control services were not significantly affected by the implementation of these margins, and more mobile species were less impacted by margins introduction. Locally foraging species were found to be more affected by the presence of margins and the specific vegetation composition compared to far-ranging species. Additionally, there was no observed competition between foragers. The study concludes that margins effectively support insect populations and can be adapted further to meet local conservation needs or provide pest control services.
The effects of semi-natural habitats on integrated pest management and biodiversity enhancement in arable agriculture
Keywords: Semi-natural habitats; Arable margins; Biodiversity; Pest management; Vegetation mixes